Variations in Mechanisms of Injury for Children with Concussion - Haarbauer-Krupa, Juliet (J Pediatr, 2018)
OBJECTIVES: To assess the distribution of injury mechanisms and activities among children with concussions in a large pediatric healthcare system. STUDY DESIGN: All patients, age 0–17 years, who had at least 1 clinical encounter with an International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis of concussion in the Children’s Hospital of Philadelphia’s electronic health record system from July 1, 2012 to June 30, 2014, were selected (N = 8233) and their initial concussion-related visit identified. Approximately, 20% of the patients (n = 1625) were randomly selected for manual record review to examine injury mechanisms and activities. RESULTS: Overall, 70% of concussions were sports related; however, this proportion varied by age. Only 18% of concussions sustained by children aged 0–4 were sports related, compared with greater proportions for older children (67% for age 5–11, 77% for age 12–14, and 73% for age 15–17). When the concussion was not sports related, the primary mechanisms of injury were struck by an object (30%) and falls (30%). CONCLUSIONS: Sports-related injuries in children older than 6 years of age contributed to the majority of concussions in this cohort; however, it is important to note that approximately one-third of concussions were from non–sports-related activities. Although there is increased participation in community and organized sports activities among children, a focus on prevention efforts in other activities where concussions occur is needed.